Endotoxin Translocation and Gut Barrier Dysfunction Are Related to Variceal Bleeding in Patients With Liver Cirrhosis - Triantos, Christos; Kalafateli, Maria; Assimakopoulos, Stelios F.; Karaivazoglou, Katerina; Mantaka, Aikaterini; Aggeletopoulou, Ioanna; Spantidea, Panagiota I.; Tsiaoussis, Georgios; Rodi, Maria; Kranidioti, Hariklia; Goukos, Dimitrios; Manolakopoulos, Spilios; et al. (Frontiers in Medicine, 2022)
Background Bacterial infections are associated with the risk of variceal bleeding through complex pathophysiologic pathways. Objectives The primary objective of the present case-control study was to investigate the role of bacterial translocation and intestinal barrier dysfunction in the pathogenesis of variceal bleeding. A secondary objective was to determine independent predictors of key outcomes in variceal bleeding, including bleeding-related mortality. Methods Eighty-four (n = 84) consecutive patients participated in the study, 41 patients with acute variceal bleeding and 43 patients with stable cirrhosis, and were followed up for 6 weeks. Peripheral blood samples were collected at patient admission and before any therapeutic intervention. Results Child-Pugh (CP) score (OR: 1.868; p = 0.044), IgM anti-endotoxin antibody levels (OR: 0.954; p = 0.016) and TGF-β levels (OR: 0.377; p = 0.026) were found to be significant predictors of variceal bleeding. Regression analysis revealed that albumin (OR: 0.0311; p = 0.023), CRP (OR: 3.234; p = 0.034) and FABP2 levels (OR:1.000, p = 0.040), CP score (OR: 2.504; p = 0.016), CP creatinine score (OR: 2.366; p = 0.008), end-stage liver disease model (MELD), Na (OR: 1.283; p = 0.033), portal vein thrombosis (OR: 0.075; p = 0.008), hepatocellular carcinoma (OR: 0.060; p = 0.003) and encephalopathy (OR: 0.179; p = 0.045) were significantly associated with 6-week mortality. Conclusions Bacterial translocation and gut barrier impairment are directly related to the risk of variceal bleeding. Microbiota-modulating interventions and anti-endotoxin agents may be promising strategies to prevent variceal bleeding.